The future of Qur'anic studies: thematic tafsir as an example - Fadzil, Ammar (Department of Qur'an and Sunnah Studies, AHAS KIRKHS, 2022)
Qur'anic studies broadly address interpretation, disciplines, and important concerns of divine scripture. This analytical descriptive chapter tries to offer a brief historical overview of writings in Qur'anic studies from its beginnings to the present, with the goal of concluding that Qur'anic studies will continue to attract the attention of researchers from all backgrounds.